Reintroduction of the giant panda into the wild: A good start suggests a bright future. (January 2018) - Yang, Zhisong; Gu, Xiaodong; Nie, Yonggang; Huang, Feng; Huang, Yan; Dai, Qiang; Hu, Yibo; Yang, Yi; Zhou, Xiao; Zhang, Hemin; Yang, Xuyu; Wei, Fuwen
Abstract: Reintroduction is an important approach in the conservation of endangered species and in recent decades a number of reintroduction programs have been conducted for conservation purposes. Generally, the success rate of reintroduction is low, but long-term monitoring of most reintroduction programs remains uncommon and this may influence the evaluation of reintroduction. The giant panda is a flagship species of biodiversity conservation. The Chinese government runs a giant panda reintroduction program and here we present reintroduction monitoring data from 2009 to 2015 for three giant pandas released into a small isolated wild population in western Sichuan, China. The results indicate that all three giant pandas display similar activity patterns to wild giant pandas, however, the wild-caught female demonstrated better adaptive ability to the wild environment than the two captive-born individuals in that she established a stable home range in the quickest time and gave birth to a cub. Genetic analysis indicates that new genetic material has been introduced into the local population. Our study provides the latest update on the giant panda introduction program and indicates that it is progressing well. Highlights: Three giant pandas were released into a small isolated wild population in western Sichuan, China. Activity rhythm, home range and genetic contribution to local giant pandas were researched. All three giant pandas display similar activity patterns to wild giant pandas. The wild-caught female demonstrated better adaptive ability to the wild environment than the captive-born individuals.